Transformation of Classical Law to Contemporary in Islamic-Based Marriage Law to Respond to Legal Developments in Indonesia - Jambunanda, Ahmad Jamaludin (Al Ahkam, 2023)
Marriage law is a provision that applies in regulating the marriage system itself. This research was conducted as an effort to find out the transformation of marriage law from classical to contemporary. Laws are made to regulate and provide all understanding of society in accordance with applicable norms and sanctions. Law is important in order to uphold justice for all human beings. Marriage is an important part that needs to be regulated in marriage law. Therefore, the marriage law is made on the basis of and needs in addressing every condition that occurs in household life. However, each of these draft ideas or rules will be agreed upon by the Regional Representatives Council (DPR). The DPR has the right to amend and draft a new law. Likewise, marriage law needs to be transformed in order to produce a more developed design. Marriage law needs to be regulated both in state law and Islamic law, both of which have an important position so that the agreed draft does not favor one applicable law. In addition, classical legal drafts need to be updated in accordance with the progress of civilization